Autophagy-lysosomal pathway is involved in lipid degradation in rat liver - Skop, V; Cahová, M; Papáčková, Z; Páleníčková, E; Daňková, H; Baranowski, M; Zabielski, P; Zdychová, J; Zídková, J; Kazdová, L (Physiological research, 2012)
We present data supporting the hypothesis that the lysosomal-autophagy pathway is involved in the degradation of intracellular triacylglycerols in the liver. In primary hepatocytes cultivated in the absence of exogenous fatty acids (FFA), both inhibition of autophagy flux (asparagine) or lysosomal activity (chloroquine) decreased secretion of VLDL (very low density lipoproteins) and formation of FFA oxidative products while the stimulation of autophagy by rapamycine increased some of these parameters. Effect of rapamycine was completely abolished by inactivation of lysosomes. Similarly, when autophagic activity was influenced by cultivating the hepatocytes in "starving" (amino-acid poor medium) or "fed" (serum-supplemented medium) conditions, VLDL secretion and FFA oxidation mirrored the changes in autophagy being higher in starvation and lower in fed state. Autophagy inhibition as well as lysosomal inactivation depressed FFA and DAG (diacylglycerol) formation in liver slices in vitro. In vivo, intensity of lysosomal lipid degradation depends on the formation of autophagolysosomes, i.e. structures bringing the substrate for degradation and lysosomal enzymes into contact. We demonstrated that lysosomal lipase (LAL) activity in liver autophagolysosomal fraction was up-regulated in fasting and down-regulated in fed state together with the increased translocation of LAL and LAMP2 proteins from lysosomal pool to this fraction. Changes in autophagy intensity (LC3-II/LC3-I ratio) followed a similar pattern.
Keywords: hepatocyty; Liver; Animals; Lipoproteins, VLDL; Lysosomes; chlorochin; Autophagy; Rats, Wistar; játra; lyzozomy; triglyceridy; Diglycerides; lipoproteiny VLDL; Fatty Acids, Nonesterified; Triglycerides; lipolýza; sterolesterasa; Sterol Esterase; kultivované buňky; Hepatocytes; autofagie; proteiny asociované s mikrotubuly; membránový protein 2 asociovaný s lyzozomy; asparagin; oxidace-redukce; Cells, Cultured; Lysosomal-Associated Membrane Protein 2; Male; Sirolimus; Oxidation-Reduction; kyseliny mastné neesterifikované; krysa rodu Rattus; sirolimus; Microtubule-Associated Proteins; zvířata; mužské pohlaví; Lipolysis; Asparagine; diglyceridy; Rats; Chloroquine; potkani Wistar